Decrease sensitivity of Eleusine indica treated with Paraquat and Glyphosate sub-lethal doses. Issue 4 (June 2021) - Saragih, M S R S; Purba, E; Damanik, R I
Abstract: Populations of Eleusine indica glyphosate-sensitive weed seeds taken from Polytechnic Negeri Medan Campus. This study aims to examine whether the use of sub-lethal doses of paraquat and glyphosate in three generations can cause a decrease in the sensitivity of the Eleusine indica population to each herbicide. This research was carried out at the Universitas Sumatera Utara Campus with a height of ± 25 m above sea level. This study used a paraquat herbicide under the recommended dosage of 200 g.a.i. ha −1 and glyphosate herbicide under the recommended dose 360 g.a.i. ha −1 with three replications. Data analysis using IBM SPSS Statistics 20 software.